Comprehensive definition of Ser/Thr/Tyr phosphorylation in mycobacteria: towards understanding reprogramming of normal macrophage function by pathogenic mycobacteria - Nakedi, Kehilwe Confidence (Division of Chemical and Systems Biology, 2019)
Mycobacterium tuberculosis, the causative agent for the disease Tuberculosis, is a serious public health problem that is responsible for 1.6 million deaths each year. The WHO’s recent report on Tuberculosis estimates that a third of the world’s population is latently infected with the bacteria, and, of those, 10% will progress to active disease. M. tuberculosis is a successful pathogen mainly due to its ability to adapt and survive in changing environments. It can survive a dormant state with limited metabolic activity during latent infection, while also being able to escape the macrophage and disseminate into active disease. Efforts to eradicate the disease must be based on understanding the biology of this organism, and the mechanisms it uses to infect, colonize, and evade the immune system. Understanding the behaviour of pathogenic mycobacteria in the macrophage is also important to the discovery of new drug targets. In this thesis, we employed state of the art mass spectrometry techniques, which allowed us to unpack the biology of this bacterium in different growth environments and expand our understanding of the mechanisms it employs to adapt and survive. We investigated protein regulation by the process of phosphorylation, through sensory kinases, which add a phosphate group to a protein of interest, thereby regulating its function. First, we interrogated the phosphoproteomic landscape between M. bovis BCG and M. smegmatis to explain how differential protein regulation results in the differences between slow and fast growth of mycobacteria. Second, we focused on Protein Kinase G (PknG), which plays an important role in bacterial survival by blocking phagosome/lysosome fusion. We identified the in vivo physiological substrates of this kinase in actively growing M.bovis BCG culture. Our results revealed that this kinase is a regulator of protein synthesis. We then examined the mechanisms of survival in murine RAW 246.7 macrophages mediated by PknG, using M. bovis BCG reference strain and PknG knock-out mutant. Our results indicated strong evidence that pathogenic mycobacteria disrupt the macrophagic cytoskeleton, through phosphorylation of proteins that are involved in cytoskeleton rearrangement. These results explain the strategies that pathogenic mycobacteria employ mediated by PknG to block phagosome-lysosome fusion and evade the host immune system and survive for prolonged periods in the macrophages. The findings of this thesis contribute to our understanding of the physiology of pathogenic mycobacteria and their interaction with the host.